Incumbents’ re-election incentives and financial report disclosure in Indonesian local government - Retno Yuliati; Athalia Ariati Hidayat; Taufik Raharjo (Sebelas Maret Business Review, 2023)
This study investigates the relationship between incumbents' re-election incentives and financial reporting disclosure in the Indonesian local government. This study uses a sample of 351 local governments at the city or district level throughout 2015-2017 when they ran a local election. Content analysis is used to assign scores to the extent of disclosure. The incumbent mayor or regent who runs a second election is signaled by 1 and 0 otherwise as the proxy for the incumbent's re-election incentives. Cross-sectional multiple regressions will be conducted to examine the hypothesis that there is a significant relationship between an incumbent's re-election incentives and disclosure of financial statements in the local government. Our findings show that incumbent re-election incentives do not have a relationship with the disclosure of financial reports. The incumbent incentive to be re-elected does not necessarily drive an incumbent to disclose its financial statements. Regarding the control variables, significant negative relationships exist between dependencies and the size of the local government towards disclosure level. However, the complexity of the population was positively related to the disclosure level of financial reports. On the contrary, political competition, debt ratio, and type of local government were not related to the disclosure level of the local government's financial reports.